Neisseria lactamicus sp. n., a Lactose-fermenting Species Resembling Neisseria meningitidis - Hollis, Dannie G. (1969)
The biochemical and serological characteristics of lactose-utilizing strains of Neisseria were determined. These organisms were found in the nasopharynx of man and grew well on Thayer-Martin Selective Medium. They were compared with N. meningitidis to ascertain whether they were variants of this species. Differences between the lactose-using strains and the recognized species of Neisseria were considered significant enough to warrant designation of a new species, Neisseria lactamicus. This group has not been widely recognized as being separate from N. meningitidis; therefore, the normal incidence and clinical significance of these organisms has not been fully established. These organisms are oxidase-positive and positive for β-D-galactosidase activity; they demonstrate fermentation in King Oxidation-Fermentation Medium; and they produce acid from only glucose, lactose, and maltose, of the 27 substrates incorporated in Cystine Trypticase Agar. Individual strains vary in their ability to grow on Nutrient Agar at both 25 and 37 C and in their pigmentation on Loeffler Medium. Results indicated that these organisms are serologically distinct from the N. meningitidis serogroups. Only 34 of 116 strains of N. lactamicus were smooth and could be tested by slide agglutination. None of the 34 could be grouped as N. meningitidis group A, B, C, D, X, Y, or Z. Thirty-one of these strains could, however, be specifically grouped with antisera prepared with N. lactamicus strains. Cross absorptions confirmed that N. lactamicus is serologically distinguishable from N. meningitidis.